Molecular Characteristics of the Equine Periodontal Ligament - Pöschke, Antje; Krähling, Bastian; Failing, Klaus; Staszyk, Carsten (Frontiers in Veterinary Science, 2018)
The equine periodontal ligament (PDL) is a fibrous connective tissue that covers the intra-alveolar parts of the tooth and anchors it to the alveolar bone — it therefore provides a similar function to a tendinous structure. While several studies have considered the formation and structure of tendons, there is insufficient information particularly on the molecular composition of the PDL. Especially for the equine PDL, there is limited knowledge concerning the expression of genes commonly regarded as typical for tendon tissue. In this study, the gene expression of e.g. collagen type 1 alpha 1 [COL1], collagen type 3 alpha 1 [COL3], scleraxis [SCX]) and fibrocartilage markers was examined in the functional mature equine PDL compared with immature and mature equine tendon tissue. PDL samples were obtained from incisor, premolar and molar teeth from seven adult horses. Additionally, tendon samples were collected from four adult horses and five foals at different sampling locations. Analyses of gene expression were performed using real-time quantitative polymerase chain reaction (qRT-PCR). Significantly higher expression levels of COL1 and 3 were found in the mature equine PDL in comparison with mature tendon, indicating higher rates of collagen production and turnover in the mature equine PDL. The expression levels of SCX, a specific marker for tenogenic-differentiated cells, were on a similar level in functional mature PDL and in mature tendon tissue. Evidence of chondrogenic metaplasia, often found in tendon entheses or in pressurized regions of tendons, was not found in the mature equine PDL. The obtained results justify further experiments focused on the possible use of equine PDL cells for cell-based regenerative therapies.